Maternal parenting and social, school, and psychological adjustment of migrant children in urban China. (November 2015) - Zhao, Siman; Chen, Xinyin; Wang, Li
This study examined the relations of maternal warmth, behavioral control, and encouragement of sociability to social, school, and psychological adjustment in migrant children in China. The participants were 284 rural-to-urban migrant children ( M age = 11 years, 149 boys) in migrant children's schools and their mothers. Data on parenting were collected from mothers' reports. Data on children's adjustment were collected from multiple sources including peer assessments, teacher ratings, self-reports, and school records. It was found that maternal warmth was associated with children's social and school performance, and that maternal encouragement of sociability was associated with children's psychological adjustment. Maternal behavioral control was not associated with children's adjustment. The results indicate that maternal warmth, behavioral control, and encouragement of sociability may serve different functions in different domains of adjustment among migrant Chinese children.